2007
DOI: 10.1016/j.jchromb.2006.08.052
|View full text |Cite
|
Sign up to set email alerts
|

Development of an at-line method for the identification of angiotensin-I inhibiting peptides in protein hydrolysates

Abstract: A fast at-line method was developed for the identification of ACE inhibiting (ACEI) peptides in protein hydrolysates. The method consists of activity measurements of fractions collected from a two-dimensional HPLC fractionation of the peptide mixture followed by MS identification of the peptides in the inhibiting fractions. The inhibition assay is based on the inhibiting effect of ACEI peptides on the hydrolytic scission of the substrate Hippuric acid-His-Leu (HHL) during the ACE-catalysed hydrolysis reaction.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 23 publications
1
11
0
Order By: Relevance
“…The results of the bioactivity assessment of the peptides are in agreement with the findings of other groups; for example, Henda et al (2013) reported an IC 50 value of 0.0151 ± 0.005 µM for captopril and Stanton (2011) reported the IC 50 value of LKP as 0.32 µM. Different IC 50 values have been reported for IPP, varying from 1.89 to 5 µM (Siltari, Viitanen, Kukkurainen, Vapaatalo, & Valjakka, 2014;van Platerink, Janssen, & Haverkamp, 2007). It has been reported that peptides with specific amino acids at the N-and C-terminus have shown variable inhibition activity with ACE (Iwaniak, Minkiewicz, & Darewicz, 2014).…”
Section: Discussionsupporting
confidence: 88%
“…The results of the bioactivity assessment of the peptides are in agreement with the findings of other groups; for example, Henda et al (2013) reported an IC 50 value of 0.0151 ± 0.005 µM for captopril and Stanton (2011) reported the IC 50 value of LKP as 0.32 µM. Different IC 50 values have been reported for IPP, varying from 1.89 to 5 µM (Siltari, Viitanen, Kukkurainen, Vapaatalo, & Valjakka, 2014;van Platerink, Janssen, & Haverkamp, 2007). It has been reported that peptides with specific amino acids at the N-and C-terminus have shown variable inhibition activity with ACE (Iwaniak, Minkiewicz, & Darewicz, 2014).…”
Section: Discussionsupporting
confidence: 88%
“…The ACE inhibition experiments were performed with an HPLC‐UV at‐line assay using the artificial substrate HHL as described previously (van Platerink and others 2007). Briefly, dipeptide samples (40 μL) at concentrations of 20 and 200 μM were pipetted into a 96‐well plate and 27 μL of the ACE solution (33.4 mU/mL in PBS, pH 7.4; ACE activity was checked before the start of the experiment) were added to each well and incubated for 5 min on a 96‐well plate mixer at 700 RPM.…”
Section: Methodsmentioning
confidence: 99%
“…There is good evidence in the mammalian circulation that HA is metabolically stable. The tripeptides hippuryl-L-histidyl-L-leucine (van Platerink et al, 2007) and hippurylglycylglycine (Jafarian-Tehrani et al, 2000) are commonly employed as substrates for angiotensin converting enzyme (ACE; peptidyl-dipeptidase A; EC 3.4.15.1) and are hydrolyzed by dipeptidase activity leaving the stable HA. Circulating HAwill certainly be exposed to ACE since it is expressed mainly in lung, vascular endothelium and kidney (Femia et al, 2008).…”
Section: The Glycine Deportation Systemmentioning
confidence: 99%